PENETAPAN KADAR FLAVONOID TOTAL JUS BUAH DELIMA (Punica granatum L.) YANG BERPOTENSI SEBAGAI HEPATOPROTEKTOR DENGAN METODE SPEKTOFOTOMETRI UV-VIS - Suharyanto Suharyanto; Anisa Dinda Ramadhani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Pomegranate is one of the plants of the Lythraceae family. Pomegranate plants are spread from the subtropics to the tropics, from the lowlands to altitudes below 1000 masl. Pomegranate contains flavonoid compounds that can be used as traditional medicine for hepatoprotectors. The aim of the researcher was to determine the total flavonoid levels in pomegranate juice (Punica granatum L) by UV-Vis Spectrophotometry. The method used in the study is the Chang method. Identification of flavonoids with concentrated HCl reagents and magnesium metal causes a change in color to red which indicates a positive sample containing flavonoids. The results of the study showed total flavonoid levels contained in pomegranate juice 0.0075766% QE. Results Variation Coefficient Value (% KV) of the sample is 0.7475%, Variation Coefficient (% KV) is the percentage ratio between the standard deviation and the average. % KV is used in grading to express precision.